Two dimensional porous 3d–4f heterometallic coordination polymers constructed by pyridine-2, 3-dicarboxylic acid1. Issue 20 (28th May 2015) - Yang, Ting-Hai; Silva, Ana Rosa; Shi, Fa-Nian
<x xml:space="preserve">Abstract</x> Four porous CoIIILnIII 3d–4f heterometallic coordination polymers constructed by the pydcH2 ligand were hydrothermally synthesized and characterized. The adsorption and catalytic properties of compound CoIIIDyIII were investigated.